Intra-articular antimicrobial therapy and lavagae for the management of arthritis in claves - Ganesh G (Department of Veterinary Surgery and Radiology, College of Veterinary and Animal Sciences, 2008)
The present study was carried out in twelve calves affected with arthritis under six months of age belonging to either sex, presented to the College Veterinary Hospitals at Mannuthy and Kokkalai. Based on the nature of synovia, whether it was non-purulent or purulent, the calves were divided into two groups viz. Group I and II, each consisting of six calves and were serially numbered from 1 to 6. Animals in Group I were treated by intra-articular antimicrobial therapy and in Group II by lavaging the affected joint with ten per cent DMSO using ‘through-and-through’ needle technique with supplementation of parentral antibiotic therapy to the animals of both the groups. Both male and female, Holstein-Friesian cross and Jersey cross bred calves with age group ranging from five days to two months were presented. In all the calves, the knee joint was affected, either unilaterally or bilaterally. Out of the 12 calves, four had the history of umbilical infection and in which the umbilical cords were torn naturally at the time of birth and the stumps were left untreated. The duration of illness ranged from two days to one week. The affected joints were swollen, warm to touch and evidenced pain on palpation with difficulty in flexing the joint. In a few calves purulent exudation was coming out. In Group I, all the calves recovered within five days of treatment except one which also got recovered, but only after two months. In Group II, promising recovery was observed in two calves within fifteen days of observation and in one recovery with persistent ankylosis, while two calves succumbed during the observation period. The mean rectal temperature, pulse rate, respiratory rate, haemoglobin concentration and VPRC were found within normal range in both the groups, throughout the period of study. The mean total leukocyte count was higher before treatment in both the groups and it was within the normal range from the fifth and fifteenth day of observation in Group I and II respectively. The neutrophil count was higher and the lymphocyte count was lower before treatment and almost reached towards normal range by the fifteenth day of observation in both the groups. The serum glucose and alkaline phosphatase levels were within the normal range throughout the period of observation in both the groups. In Group I, the synovia was yellowish, odourless and with normal to fair mucin clot quality and prolonged clotting time. In Group II, it was turbid yellow with flocculent materials and pungent odour (in two cases) with fair to very poor mucin clot quality and quickened clotting time. The mean glucose levels were within the normal range in Group I and lower in Group II. But the mean alkaline phosphatase level was observed to be higher than the levels obtained in serum in both the groups. Escherichia coli was the major organism isolated from two samples of synovial fluid among the twelve samples collected and gentamicin was sensitive in one isolate, while Sulphadiazine in the other one. In Group I, the affected joints were without any characteristic radiographic abnormalities except for the increase in soft tissue density due to soft tissue swelling. Whereas in Group II lesions identified were widened joint space, intra-articular gas shadow, subchondral osteolysis and blurring of normal bone outline. There were not many variations in the fifteenth day post-treatment radiographs. Histopathology of affected joint was performed in two calves which succumbed during the observation period. Macroscopic examination revealed considerable swelling of joint with pus and degeneration of articular cartilage. Microscopic examination revealed thick hyalinised fibrocollagenous tissue, areas of haemorrhage with many congested blood vessels. Some areas appeared like abscess wall of which was formed by inflammatory granulation tissue. One section showed bony tissue with degenerating bony trabeculae. Periosteum and adjacent tissues showed extensive necrosis and abscess formation.